2016
DOI: 10.1097/brs.0000000000001678
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Combined Multimodality Somatosensory Evoked Potential and Transcranial Motor Evoked Potential Intraoperative Monitoring in Patients With Idiopathic Scoliosis

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 25 publications
1
34
0
6
Order By: Relevance
“…Stabilizing the hemodynamic status resulted in recovery of TcMEPs. A new postoperative neurological deficit was only seen in one surgery with INM (1.6%), in one child of 56 (1.8%): this is similar to the 1.38% deficit reported in a systematic review of the diagnostic accuracy of motor evoked potentials to detect neurological deficits during idiopathic scoliosis correction ( Thirumala et al, 2017 , Thirumala et al, 2016 ). There were no new neurological deficits without an alert during INM and other studies ( Ferguson et al, 2014 ) have also suggested that INM has a 100% negative predictive value.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Stabilizing the hemodynamic status resulted in recovery of TcMEPs. A new postoperative neurological deficit was only seen in one surgery with INM (1.6%), in one child of 56 (1.8%): this is similar to the 1.38% deficit reported in a systematic review of the diagnostic accuracy of motor evoked potentials to detect neurological deficits during idiopathic scoliosis correction ( Thirumala et al, 2017 , Thirumala et al, 2016 ). There were no new neurological deficits without an alert during INM and other studies ( Ferguson et al, 2014 ) have also suggested that INM has a 100% negative predictive value.…”
Section: Discussionsupporting
confidence: 80%
“…We undertook 61 INMs with TcMEPs and SSEPs in 56 children having scoliosis and spine deformity surgery, with no adverse effects from the INM. TcMEP is a highly sensitive and specific tool for detecting spinal cord motor impairment or injury during spine surgery ( Kim et al, 2013 , Legatt et al, 2016 , Thirumala et al, 2016 , Thirumala et al, 2017 , Kelleher et al, 2008 ). Previous studies ( Legatt et al, 2016 ) have reported predominantly minor injuries in <0.2% of patients having INM.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 , 5 , 12 14 ] Surgery for SBFD remains technically demanding due to the potential risk of postoperative neurological deterioration such as sensory loss, lower limb weakness, and even paralysis. At present, MIOM has been widely utilized to prevent neurological compromise in scoliosis correction [ 15 ] and intramedullary tumor resection surgery. [ 16 , 17 ] MIOM data has been trusted by various authors.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 , 17 ] MIOM data has been trusted by various authors. [ 8 , 9 , 15 19 ] However, no studies have focused on the intraoperative spinal cord function detected by MIOM during the reduction of the fracture and dislocation. Therefore, the present study was conducted to estimate the feasibility of MIOM on SBFD patients in PRI surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Contraindications mainly include (1) L5-S1 lumbar disc herniation due to the high ilium which affects the installation of the channel, 2 INM has been commonly utilized to avoid nerve damage in spinal surgery [9,19], and considered by many scholars as a reliable method to avoid nerve injury [9,19,20]. Even if there are no neuromonitoring events during the operation, we believe that it is necessary to monitor the functional state of the nerve root, especially in the process of channel installation.…”
Section: Indications Of This Technique Include (1) Ldh With Segmentalmentioning
confidence: 99%